PENGEMBANGAN SISTEM PERUBAHAN KARTU RENCANA STUDI BERBASIS ANDROID PADA STMIK KHARISMA MAKASSAR - George Lomowa; Syaiful Rahman; Junaedy (JTRISTE, 2018)
Study Program Card is something that owned by every college student. On every end of semester, college student must submit their Kartu Rencana Studi for their next semester. Sometimes college students also made a mistake when they submitted their Kartu Rencana Studi then they need to resubmit or change their Kartu Rencana Studi. The purpose of this research is to develop an Android-Based system for changing study program card on STMIK Kharisma Makassar that can help the student and college staff. There are method that writter use for this research such as Rapid Application Development for the process of developing this system and Black Box Testing for testing the system input-output. The result of this research is the author has successed for developing android-based system for changing study program card that can be used in STMIK Kharisma Makassar.